The power of ethnographic toolkit in understanding transnational culture - Dogan Akkaya, Fatma (SAGE Publications, 2023)
Intergenerational ethnographic research poses several practical, epistemological, and ethical challenges. This study seeks to address these complexities by encouraging researchers to construct personalised ethnographic toolkits that provide insights into uncovering the complex subjectivities of research populations through intergenerational narratives. Based on over two years of research among the Turkish community in London, the study reveals compelling examples of symbolic communication used by individuals of different generations, genders, and social roles. Using various data collection methods, including interviews, observation, drawing, and television viewing, the research illustrates how this ethnic community uses language, fashion, and religion to integrate into multicultural environments and manifest their belonging in transnational contexts. By incorporating methodological tools such as unplanned moments, reflexivity, and positionality, the study aims to understand the underpinnings of cultural identity by examining how different generations respond to social conditions shaped by migration.